HUBUNGAN KOORDINASI MATA DAN KAKI DENGAN KETERAMPILAN SEPAK SILA PERMAINAN SEPAK TAKRAW PADA TIM PPLP RIAU 2015 - Azwan, Muhamad; Juita, Ardiah; ', Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem of this research is the result of observations researchers in the field that the game of Sepak takraw of PPLP Riau Team, at the time of the bait to Smasher was often not optimal and didnot match the desired expectations. This research was conducted to determine wheter there is coordination between the eyes and legs with sila football skill of sepak takraw game in pplp riau team 2015. The samples of this research was sepak takraw team of PPLP Riau 2015, it was about 15 students. The technique to collecting of sample was total sampling. The instrument of this research was eye and legs coordination test, which aimed to measure te eye and legs coordination and sepak sila skills test, that aimed to measure the sepak sila skill. And then, anayzing the statistics to test normality with lilifors test in significant 0,05α. Hypothesis asked was suspeccted there was correlation the eye and legs coordintion in sepak sila skill in takraw game at PPLP Riau team 2015. Based on lilisfor analysis resulted Lcount (x) about 0,138 and Ltabel0,220, Lcount(y) about 0,084 and Ltabel 0,220 so, Lcount<Ltable, so the samples come from the population of normal distribution. Then, the correlation result product moment between eye and legs coordinaton with sepak sila resulted rcount 0,682 and rtable 0,532 so rcount>rtable effected Ho received and Ha rejected . So, there is the significant correlation between eye and legs coordinaton with sepak sila of takraw game at pplp riau team 2015.Keywords: eye and legs coordination, sepak sila skill